2008
DOI: 10.1016/j.humpath.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of conventional cytology, DNA ploidy analysis, and fluorescence in situ hybridization for the detection of dysplasia and adenocarcinoma in patients with Barrett's esophagus

Abstract: SummaryNew detection methods with prognostic power are needed for early identification of dysplasia and esophageal adenocarcinoma (EA) in patients with Barrett's esophagus (BE). This study assessed the relative sensitivity and specificity of conventional cytology, DNA ploidy analysis with digital image analysis (DIA), and fluorescence in situ hybridization (FISH) for the detection of dysplasia and adenocarcinoma in endoscopic brushing specimens from 92 patients undergoing endoscopic surveillance for BE. FISH u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 28 publications
(32 reference statements)
2
70
0
Order By: Relevance
“…13 Others report similar rates of ErbB2 positivity in oesophageal adenocarcinomas, highlighting the impact of ErbB2 amplification and ERBB2 overexpression during the malignant progression of Barrett's metaplasia to invasive cancer. [27][28][29] The relatively high number of ErbB2-positive cases in our study compared with other reports may be due to the definition of ErbB2 positivity, which was based on the guidelines of the ToGA study and the EMEA for trastuzumab (Herceptin r ) treatment for advanced gastric cancer. This recommendation requires a ErbB2 score of 3 þ by immunohistochemistry or an amplification level of Z2 (ErbB2/Chr17) even in small tumour cell clusters, 10 which is different from the breast carcinoma requirements, in which cases with a ErbB2/ Chr17 ratio between 1.8 and 2.2 are considered as equivocal and ErbB2 expression is less heterogeneous.…”
Section: Discussionmentioning
confidence: 63%
“…13 Others report similar rates of ErbB2 positivity in oesophageal adenocarcinomas, highlighting the impact of ErbB2 amplification and ERBB2 overexpression during the malignant progression of Barrett's metaplasia to invasive cancer. [27][28][29] The relatively high number of ErbB2-positive cases in our study compared with other reports may be due to the definition of ErbB2 positivity, which was based on the guidelines of the ToGA study and the EMEA for trastuzumab (Herceptin r ) treatment for advanced gastric cancer. This recommendation requires a ErbB2 score of 3 þ by immunohistochemistry or an amplification level of Z2 (ErbB2/Chr17) even in small tumour cell clusters, 10 which is different from the breast carcinoma requirements, in which cases with a ErbB2/ Chr17 ratio between 1.8 and 2.2 are considered as equivocal and ErbB2 expression is less heterogeneous.…”
Section: Discussionmentioning
confidence: 63%
“…It is a common molecular pathological characteristic in human carcinoma (7,15,16). A number of studies have suggested that using DNA probes for the detection of aneuploidy in cancer cells may be a superior technique to conventional pathological diagnosis (8)(9)(10)(11)(12)14). Han et al examined 113 EC patients using specific centromere DNA probes 3, 8, 10, 12, 17 and 20, and found that chromosomal signal numbers and all chromosomes were found to have abnormal copy numbers (12).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant cells are therefore capable of being diagnosed by detecting aneuploidy, usually found in aneusomic nuclei. Fluorescence in situ hybridization (FISH) technology is a rapid and sensitive method for detecting aneusomy of a specific chromosome and is widely used in the diagnosis of hematological malignancies, lung, breast and kidney cancer, with high sensitivity and specificity (8)(9)(10)(11). The advantage of the FISH method has been considered to lie in its objective and quantitative evaluation of malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of high-grade dysplasia (HGD) in BE patients may lead to radical therapeutic interventions such as esophagectomy or endoscopic mucosal resection, and RFA treatment. [15][16][17] Some recent studies investigated the use of fluorescence in situ hybridization (FISH) for the detection of dysplasia, 18 and the potential molecular biomarkers for EAC progression, 19,20 including epigenetic phenomena. 21,22 Although these attempts may hold promise, the diagnostic interpretation and histological grading of key clinical decision points in BE, including negative for dysplasia (NFD), LGD, and HGD, remains problematic.…”
mentioning
confidence: 99%
“…[35][36][37] In tissue-based BE research, some researchers have investigated alternative computerized morphometry and texture measurements as indicators for disease progression. 18,38,39 Nonetheless, the majority of other studies are still focusing on the well-established DNA density measurements using tissue sections (e.g., 3-7 μm), especially the use of the commercially available ACIS system (Automated Cellular Imaging System, Dako, Denmark) from a field of view (FoV) of tissue sections. [40][41][42][43][44] Under a microscope at × 40 magnification, a FoV is digitally captured followed by image analysis to locate nuclei and to measure the integrated optical density (IOD) for each nucleus.…”
mentioning
confidence: 99%